CETA investment law : article-by-article commentary. (London [England] : NOMOS HART, 2021)
"This article-by-article Commentary on the Canada-European Union Comprehensive Economic and Trade Agreement (CETA) is a vital resource for practitioners and academics in the field of EU investment protection law. CETA has been called a game-changer. In the investment chapter, it has introduced a number of key innovations, including; - the investment court system with an appellate tribunal, - guidelines on third party funding, - transparency and information sharing, - modern versions of standards of protection, and - detailed provisions on reservations and exceptions. Considering that the new dispute resolution provisions in this chapter have also passed the scrutiny of the Court of Justice of the European Union, it is expected that CETA's investment chapter will serve as a blueprint for future EU investment agreements and so a full understanding of this, offered by this useful commentary, is essential for lawyers."--
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law; Electronic books